Guinea- Bissau : Technical Assistance Report-External Sector Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2020)
A technical assistance (TA) mission on external sector statistics (ESS) visited Guinea-Bissau during February 3 to 7, 2020. The mission was conducted in Bissau at the request of the National Directorate for Guinea-Bissau of the Central Bank of West African States (BCEAO-DNGB). The mission assisted in improving the quality of ESS. This was the fourth and final mission under the JSA-AFR project for improving ESS in 17 francophone countries of Central and West Africa, financed by the government of Japan and administered by the IMF.